A pilot randomized controlled trial of a stepped care intervention package for depression in primary care in Nigeria - Oladeji, Ayodele; Kola, Lola; Abiona, Taiwo; Montgomery, Alan A. (BioMed Central, 2015)
Background Depression is common in primary care and is often unrecognized and untreated. Studies are needed to demonstrate the feasibility of implementing evidence-based depression care provided by primary health care workers (PHCWs) in sub-Saharan Africa. We carried out a pilot two-parallel arm cluster randomized controlled trial of a package of care for depression in primary care.